Simulation of The Effect of Interfrency and EIRP on To DVB-S2 and DVB-RCS2 Network QOS - Saputra, Heskia Jefri; Alfatih, Faiz; Alimi, Sabri (Jurnal Teknologi, 2024)
Satellite communication technology in aircraft is used for long-distance communication between aircraft and outside parties, This study uses NS-3 as software to simulate satellite communication process and analyze QoS based on DVB-RCS and DVB-S2 technology looking at  throughput, delay, PDR parameter values. This simulation aims to obtain QoS value of data sent from the user terminal to gateway based on variations in antenna gain and to determine the effect of  interference level caused by noise on user's device on quality of data reception. Results of running from UT to GW five variations of antenna gain, namely 28, 29, 30, 33, 35 Dbi, Average throughput is 29.9301 Kbps, delay is 48.9212 s, and PDR is 29.7322%. For the results of running from GW to UT with same five variations of antenna gain and five variations of noise, is 0 db, 24.7 db, 49, 7db, the throughtput results are 203.549 Kbps with delay of 0, 263834 s, and PDR is 99.91%. The conclusion obtained is that simulation using NS-3 simulator tool with an antenna amplifier has increased throughput, delay, and PDR as well as service quality and level of user interference is stable and doesn’t experience a decrease in package delivery.